2021
DOI: 10.21203/rs.3.rs-1036026/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide Analysis of the MADS-Box Gene Family in Foxtail Millet (Setaria Italica L.) and Expression Analyses to Reveal Their Role During Drought Stress

Abstract: MADS-box gene family is a key regulatory factor family, which controls vegetative growth, reproductive development and can be used to mediate abiotic stresses in many plants. However, Knowledge of this gene family is still limited in Setaria italica. In the present study, a total of 70 SitMADS genes were identified and renamed on the basis of the chromosomal distribution of the SitMADS genes. According to gene structure, conserved motif and phylogenetic feature, the 70 SitMADSs were classified into type-Ⅰ (Mα,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Studies have found that MADS-box gene is involved in a variety of hormone processes, indicating that plant hormones regulate MADS-box gene in a variety of ways, and there may be synergism or antagonism among different plant hormones Song et al, 2023). At present, the regulatory role of MADS-box in some plant hormones (such as ABA, BR) and drought stress signal transduction has been proved (Duan et al, 2006;Shao et al, 2010;Ma, 2022), but its role in other hormones and stress signal transduction has not been reported. At the same time, the presence of a response element in the MADS-box gene containing the K-box domain is not necessarily induced by the corresponding hormone or environment, on the contrary, some response elements lacking in the MADS-box gene containing the K-box domain can also be induced by the corresponding hormone or environment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that MADS-box gene is involved in a variety of hormone processes, indicating that plant hormones regulate MADS-box gene in a variety of ways, and there may be synergism or antagonism among different plant hormones Song et al, 2023). At present, the regulatory role of MADS-box in some plant hormones (such as ABA, BR) and drought stress signal transduction has been proved (Duan et al, 2006;Shao et al, 2010;Ma, 2022), but its role in other hormones and stress signal transduction has not been reported. At the same time, the presence of a response element in the MADS-box gene containing the K-box domain is not necessarily induced by the corresponding hormone or environment, on the contrary, some response elements lacking in the MADS-box gene containing the K-box domain can also be induced by the corresponding hormone or environment.…”
Section: Discussionmentioning
confidence: 99%